Einsatz der Pedobarographie zur Kontrolle und Korrektur einer vorgegebenen Teilbelastung in der orthopädisch-traumatologischen Rehabilitation - Jöllenbeck, T.; Bauer, S. (Messplätze, Messplatztraining, motorisches Lernen: ausgewählte Beiträge; 5. gemeinsames Symposium der dvs-Sektionen Biomechanik, Sportmotorik und Trainingswissenschaft; Universität Leipzig, Sportwissenschaftliche Fakultät, 19. bis 21. September 2002 / Veranst.: Sportwissenschaftliche Fakultät der Universität Leipzig ..., 2003)
Observance of a given partial loading is an essential criterion of safety and success in the orthopedic rehabilitation. In practice adjustment, observance and correction of partial loading is realized insufficient in most cases because of missing suitable measuring instruments. For that purpose in the present study the use of pedobarography was investigated. Eight patients were examined twice in an interval of one week. Results show that in spite of just before realized adjustment all patient considerably exceed their partial loading of about 70 %. Additionally they show distinct variations of partial loading of about 60 % around mean in step by step analysis. The determined measurement error of pedobarography of about 5-10 % is neglectable in first order and the method a valuable help.